Armenian national divisions on the Stalingrad and Caucasian fronts - Melkonyan, Ashot A.; Avanesyan, Iskuhi N.; Makaryan, Lilit A. (Journal of the Belarusian State University. History, 2026)
The Great Patriotic War of the Soviet Union was a severe challenge for all the peoples of the union, including the Armenian people. From the very first days of the war, Soviet Armenia began work on realising the republic’s military potential. It faced extremely important tasks: first of all, to reorganise all its activities on a military basis, to ensure mobilisation, to recruit personnel to replace those who had gone to the front, and to continue the work of the rear without interruption. After all this, it was necessary to organise military training for the population, form a people’s militia, build defensive fortifications in border areas, etc. The formation of national divisions played an important role in the mobilisation work carried out in the first period of the war. This article aims to highlight key historical moments involving Armenian divisions during the Battle of Stalingrad and the defence of the Caucasus. Research indicates that these divisions endured a challenging combat path throughout the Great Patriotic War, contributing significantly to the defeat of Nazi forces through courage and self-sacrifice. The findings show that Armenian divisions played a crucial role in the Battle of Stalingrad, an event that proved decisive for the outcome of the Great Patriotic War and World War II overall, as well as in the defence of the Caucasus, which helped prevent an enemy advance into Soviet Armenia.
Keywords: fascism; Great Patriotic War; mobilisation; Armenian divisions; combat path; Battle of Stalingrad; Caucasian front